PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DALAM UPAYA MENINGKATKAN JUMLAH WAKTU AKTIF BELAJAR SISWA : Penelitian Tindakan Kelas di Sekolah Dasar Negeri 1 Rumpin - Aip Purqon Muhyadi, - (2012)
The research was motivated by the lack of active learning time students in physical education, so it was not conducive learning atmosphere, the students are less enthusiastic and less excited. By using the cooperative learning model that emphasizes the attitude of mutual cooperation and to facilitate complete the tasks given also the amount of time spent is more effective and efficient. The research focused on the implementation of cooperative learning model in an effort to increase the number of active learning time students in Rumpin Elementary School. The research method used was Class Action Research description of qualitative and quantitative model of Kemmis and Taggart cycles with planning steps, action, observation, and reflection. The purpose of this research was to gain an overview of implementation of cooperative learning model in effort to increase the number of active learning time students. From the results of the evaluation of cooperative learning process was done at 5th class starting from the cycle I (actions 1 and 2) to the cycle II (actions 1 and 2) seen a significant increase of each cycle and the action that is : for category A (which is the management or regulation of students) increased from 53.3% to 65.27% to 72.7% to 80% and to 81.38%, for category B (which is a command or instruction) increased from 54.4% to 65.83% to 73% to 79.1% and to 81.11%, for category C (which is active time used) increased from 54.1% to 63.88% to 74.1% to 78.3% and to 81.94%, for category D (which is waiting for the opportunity and teachers instructions) increased from 55.8% to 61.11% to 73% to 78.8% and to 80.83%. Thus the implementation of cooperative learning model could to increase the number of active learning time students.